In vivo slit scanning confocal microscopic observation in a patient with keratoconus wearing miniscleral contact lens for one year: a case report - Ghosh, Somnath; Haliza Abdul Mutalib,; Sharanjeet Kaur,; Rituparna Ghoshal, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of the present case report was to evaluate corneal microstructure in a patient with keratoconus wearing miniscleral contact lens (MS CL) for 1 year. A 38 years old patient diagnosed with stage III keratoconus in right eye and corneal graft (penetrating keratoplasty) in left eye was referred to optometry department of a public hospital in Malaysia. Based on the MS CLs fitting performance on the patient’s eye, MS CLs were prescribed in both eyes. However, patient opted for MS CL only in the right eye. In vivo slit scanning confocal microscopy was performed at baseline and after 1 year of contact lens wear in right eye. Qualitative analysis was done using a grading scale designed by Hollingsworth et al. (2005a), while quantitative analysis was performed using NAVIS software in a fixed frame of 0.06 mm². After 1 year of MS CL wear, qualitative observation of right cornea showed no change in stromal haze and architecture of nerve fibers. However, morphological alterations like dark bands were observed both in anterior and posterior stroma along with tendency of clustering keratocyte nuclei in posterior stroma. Quantitative analysis showed that anterior and posterior stroma keratocyte density and endothelium cell density were relatively low after 1 year of MS CL wear (817.3, 667.2, and 2577 cells/mm², respectively) caompared to baseline observation (850.7, 705.0, and 2666 cells/mm², respectively). Mean cell area of anterior stroma, posterior stroma and endothelium were also different in post MS CL wear. Polymegathism and pleomorphism calculated by NAVIS software were varied after 1 year (49.6% and 37.5%, respectively) compared to baseline (67.1% and 29.6%, respectively). In the discussed case, noticeable changes were observed in corneal microstructure after 1 year of MS CL wear. Thereby, in conclusion we recommend future studies with more number of keratoconic eyes wearing MS CLs to emphasize the findings on microstructural changes in keratoconic cornea wearing MS CLs.